REFORMASI SISTEM ADMINISTRASI KEPEGAWAIAN MENUJU NETRALITAS PEGAWAI NEGERI SIPIL - Muhammad Basri (Badan Kepegawaian Negara | The National Civil Service Agency, 2009)
Bureaucracy, inside which the civil servants are, is one of important political structure in democratizion process.Tendency which has happened, during the period of New Order Government was that bureaucracy became political power machine in order to justify all government policies but the government reform does not choices except to personnel adinistrative reform go in the direction of neutrality of civil servan by mean of three policies, regulation reform of government official, human resource development of civil servan prosferity improvement. Key words: Administrative reform, civil servan neutrality, empowerment